Preliminary validation of the 15-item WHO ageism experiences scale in a mixed-age UK sample - Aja Louise Murray; Xuefei Li; Tom Booth (PLoS ONE, 2026)
Background Ageism, defined as stereotypes, prejudices and discrimination based on a person’s age is prevalent and negatively impacts individuals and society. In 2016, the World Health Organization (WHO) received a mandate from its Member States to lead the global campaign to combat ageism. However, success in combating ageism is critically dependent on the availability of valid and reliable measures of people’s experiences of ageism that can capture its multidimensional nature and as it is directed against multiple age groups across diverse country settings. The goal of current study is to present a preliminary psychometric validation of a measure specifically designed to meet this need: the 15-item WHO Ageism Experiences Scale. The scale includes items measuring self-directed, interpersonal, and institutional ageism and spans stereotypes, prejudices, and discrimination. Method We collected data from a UK mixed-age adult sample ( N = 402), and several psychometric properties were tested, including internal consistency reliability, test-retest reliability, and convergent validity. Results Results suggested that the 15-item WHO Ageism Experiences Scale has good internal consistency (where relevant) and test-retest reliability. The exploratory factor analysis supported a one-factor model for self-directed ageism items. The scale also proved to have adequate convergent validity. Discussion The results provide sufficient support for the adoption of the scale in this population and motivates its translation and validation in other settings, as well as the evaluation of a more extended set of psychometric properties in future studies.